2016
DOI: 10.1080/01647954.2016.1191539
|View full text |Cite
|
Sign up to set email alerts
|

Different population densities and continuous feeding byOligonychus yothersi(McGregor) (Acari: Tetranychidae) affect the emissions of herbivore-induced plant volatiles on avocado (Persea americanaMill. cv. Hass) shoots under semi-field conditions

Abstract: Plants attacked by insects and mites release blends of herbivore-induced plant volatiles (HIPVs), which act as chemical cues that attract predators and/or repel herbivores alongside alerting neighbouring plants. The chemical profiles of avocado (Persea americana Mill. Cultivar Hass) shoots infested with the foliar mite Oligonychus yothersi (Acari: Tetranychidae) were analysed using a gas chromatograph coupled to a mass spectrometer (GC-MS); the different collections of volatiles were performed under semi-field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…The graft 'Hass'/'Mexicola' emitted other monoterpenes as β-pinene, cumene, 3-carene, R-limonene and (Z)-β-ocimene, and 'Hass'/'Zutano' emitted cumene (Table 1). Rioja et al (2016) collected BVOC from intact avocado 'Hass' grafted on 'Mexicola' registering the same compounds although in different concentrations. Bravo-Monzón and Espinosa-García (2008) found that 'Hass' avocado grafted on 'Criollo' rootstock released high abundance of α-pinene, β-phellandrene, β-pinene, β-myrcene, α-cubebene, α-copaene, and β-caryophyllene.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The graft 'Hass'/'Mexicola' emitted other monoterpenes as β-pinene, cumene, 3-carene, R-limonene and (Z)-β-ocimene, and 'Hass'/'Zutano' emitted cumene (Table 1). Rioja et al (2016) collected BVOC from intact avocado 'Hass' grafted on 'Mexicola' registering the same compounds although in different concentrations. Bravo-Monzón and Espinosa-García (2008) found that 'Hass' avocado grafted on 'Criollo' rootstock released high abundance of α-pinene, β-phellandrene, β-pinene, β-myrcene, α-cubebene, α-copaene, and β-caryophyllene.…”
Section: Resultsmentioning
confidence: 99%
“…Herbivore-induced plant volatiles (HIPVs) are emitted after herbivory (Arimura et al, 2011;Gols, 2014;Heil, 2014); thus, specific odor cues are exploited by predators and parasitoids. In addition, HIPVs are modified by arthropod species, herbivores density, genotypes and plant cultivars, plant ontogeny, and abiotic factors (Hare, 2010;Hare and Sun, 2011;Proffit et al, 2011;Becker et al, 2015;Clavijo, 2016;Rioja et al, 2016).…”
Section: Scientific Notementioning
confidence: 99%
See 1 more Smart Citation
“…Eight compounds were exclusively detected in mite infested plants (Z)-3-hexen-1-ol (0.35 μg mL -1 ), 3-hexen-1-ol-benzoate (3.45 μg mL -1 ), β-myrcene (0.65 μg mL -1 ), (Z)-β-ocimene (8.11 μg mL -1 ), β-linalool (22.6 μg mL -1 ), α-farnesene (37.8 μg mL -1 ), farnesyl cyanide (18.9 μg mL -1 ) and methyl salicylate (94.1 μg mL -1 ) (Figure 1). The HIPVs identified were induced in response to O. yothersi-feeding in avocado plants (Rioja et al, 2016); those chemical compounds belong from different pathways such as GLVs, monoterpenes, sesquiterpenes and aromatic compounds, mainly. The highest emission rates were exhibited by (E)-β-ocimene, β-linalool, methyl salicylate, and α-farnesene.…”
Section: Identification Of Plant Volatile Compoundsmentioning
confidence: 99%
“…orchards in the Valparaíso Region, Chile (Rioja et al, 2015). Oligonychus yothersi feeds on the upper leaf surface, affects leaf physiological parameters, and causes reddish color and discoloration by high oxidative stress, which is a response to O. yothersi feeding on the leaf (Hoy, 2011;Rioja et al, 2016). High O. yothersi infestations are also reported between mid-summer and late autumn, whereas the O. yothersi population is not observed during rainy seasons with low temperatures and short days (winter and early spring), indicating that those abiotic factors could affect the population outbreaks at the Quillota location (Ripa and Larral, 2008).…”
Section: Introductionmentioning
confidence: 99%